ISO 25964-2: Interoperability of thesauri with other knowledge organization systems in semantic contexts - García-Marco, Francisco-Javier (Anuario ThinkEPI, 2017)
The second part of ISO 25964 on interoperability of thesauri with other knowledge organization systems is presented in the context of the Internet and semantic web. A review is offered of the main mapping models, the main semantic relation mappings, and the intricacies of mapping thesauri against bibliographical and archival classifications, taxonomies, subject heading systems, ontologies, terminologies, authority lists, and synonym rings. Finally, the implications of the ISO 25964 standard for the theory and practice of knowledge organization systems are discussed.
Keywords: Thesauri; Systems of knowledge organization; Semantic interoperability; Open data; Semantic Web; Bibliographical classifications; File classification tables; Taxonomies; Subject headings lists; Ontologies; Terminologies; Authority checklists